Problems of Justice and Social Change in India - Plamthodathil, Jacob S (Journal of Dharma, 1984)
The Indian society today (perhaps, like all other societies) is full of inequalities and, therefore, everyday one comes across human situations of injustice thwarting and preventing the development of man and presenting healthy changes in the traditional social set-up. But people have got accustomed to such situations and they have learned to ignore cases of blatant injustice and persuaded themselves that the only thing that matters is to concentrate on one's own individual well-being rather than waste time and energy on other people's problems. We shall briefly examine the forces and mechanisms behind this general attitude and indicate some ways in which this abnormal situation may be corrected.